2012
DOI: 10.1029/2012gl053736
|View full text |Cite
|
Sign up to set email alerts
|

Multi‐decadal decline of mercury in the North Atlantic atmosphere explained by changing subsurface seawater concentrations

Abstract: ) over the NA (steeper than at Northern Hemispheric land sites) but no significant decline over the SA. Surface water Hg 0 measurements in the NA show a decline of À5.7% a À1 since 1999, and limited subsurface ocean data show an $80% decline from 1980 to present. We use a coupled global atmosphere-ocean model to show that the decline in NA atmospheric concentrations can be explained by decreasing oceanic evasion from the NA driven by declining subsurface water Hg concentrations. We speculate that this large hi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
111
1

Year Published

2013
2013
2017
2017

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 104 publications
(118 citation statements)
references
References 68 publications
6
111
1
Order By: Relevance
“…). Model increases are limited to East Asia, consistent with preliminary observations and previous modeling studies (6,11,27).…”
Section: Consistency With Observed Atmospheric Trendssupporting
confidence: 74%
See 2 more Smart Citations
“…). Model increases are limited to East Asia, consistent with preliminary observations and previous modeling studies (6,11,27).…”
Section: Consistency With Observed Atmospheric Trendssupporting
confidence: 74%
“…The concentrations of major oxidants for atmospheric Hg 0 , including OH, O 3 , and Br, have remained relatively steady or slightly decreased since the mid-1990s and are thus not an important driver for the observed decline (5). Decreasing riverine discharges, which was previously speculated to drive the decline in North Atlantic Ocean Hg concentration and subsequent reemission flux (6), are also insufficient for forcing the global atmospheric trend (31,33).…”
Section: Consistency With Observed Atmospheric Trendsmentioning
confidence: 99%
See 1 more Smart Citation
“…This number can be viewed as a preliminary threshold for judging how representative the trends observed at any background site in the Southern Hemisphere are. With this threshold, much smaller trends at shorter time periods can be detected by long-term measurements at several sites when compared to shipboard measurements as reviewed by Soerensen et al (2012). Figure 4 shows an overall tendency of annual average mercury concentrations for Cape Point to increase with time.…”
Section: Comparison Of Annual Averagesmentioning
confidence: 90%
“…It also makes statistical tests for the differences of averages impossible. It is not surprising that, using such data, Soerensen et al (2012) concluded that no significant trend in the Southern Hemisphere could be detected so far. While we agree with this conclusion, a qualification is required: the quality of the data used by Soerensen et al (2012) does not allow detection of trends smaller than their variability, i.e.…”
Section: F Slemr Et Al: Comparison Of Mercury Concentrations Measurmentioning
confidence: 99%